Effects of aroeira (Schinus terebinthifoliu Raddi) oil on cutaneous wound healing in rats - Estevão,Lígia Reis Moura (2013)
PURPOSE: To evaluate the effects of aroeira (Schinus terebinthifolius) ointment on skin wound healing in rats. METHODS: Adult male rats (n=20) were divided into four groups of five animals each, as follows: G4, G7, G14 and G21, which corresponds to 4th, 7th, 14th and 21th days postoperatively. Each animal were made two incisions on the skin, including the subcutaneous tissue, in the right and left sides of thoracic region, separated by a distance of two inches. The right lesion was treated with base ointment (vaseline, lanolin); the left one was treated with base ointment containing 5% of aroeira oil. At the end of each experimental period the lesions were evaluated for the contraction degree. Then held the collection of fragments that were fixed in 10% formalin and processed for paraffin embedding. In the histological sections (5μm) was evaluated the morphology and quantified the collagen and blood vessels. The data obtained were submitted to ANOVA test complemented by Tukey-Kramer test (p<0.05). RESULTS: The contraction of the lesions was higher in wounds treated with aroeira oil than in controls at 7th and 14th days (p<0.01), whereas in the 21st day all lesions were already completely healed. The morphology showed granulation tissue more developed, with fibroblasts more bulky and collagen fibers more arranged in the experimental group at 4th, 7th and 14th days. The morphometry showed a significant increase in the quantification of collagen fibers in the experimental group at 7th and 14th days (p<0.05). CONCLUSION: The aroeira oil accelerates the healing process of wounds as a macroscopic, morphological and morphometrical analysis.